Phase II Multicenter, Open‐Label Study of Oral ENMD‐2076 for the Treatment of Patients with Advanced Fibrolamellar Carcinoma. (10th March 2020) - Abou‐Alfa, Ghassan K.; Mayer, Robert; Venook, Alan P.; O'Neill, Allison F.; Beg, Muhammad S.; LaQuaglia, Michael; Kingham, Peter T.; Kobos, Rachel; Basturk, Olca; Brennan, Cameron; Yopp, Adam; Harding, James J.; et al.
Abstract: Lessons Learned: The fibrolamellar carcinoma‐associated DNAJB1‐PRKACA gene fusion transcript RNA codes for the catalytic domain of protein kinase A and, thus, overexpression of Aurora kinase A. ENMD‐2076 showed a favorable toxicity profile. The limited results, one patient (3%) with a partial response and 57% of patients with stable disease, do not support further evaluation of ENMD‐2076 as single agent. Future studies will depend on the simultaneous targeting approach of DNAJB1‐PRKACA and the critical downstream components. Background: Fibrolamellar carcinoma (FLC) represents approximately 0.85% of liver cancers. The associated DNAJB1‐PRKACA gene fusion transcript RNA codes for the catalytic domain of protein kinase A and overexpression of Aurora kinase A (AURKA). ENMD‐2076 is a selective anti‐AURKA inhibitor. Methods: Patients aged >12 years with pathologically confirmed incurable FLC, with measurable disease, Eastern Cooperative Oncology Group performance status 0–2 or Lansky 70–100, and adequate organ function were eligible. Patients were prescribed ENMD‐2076 based on body surface area. The primary endpoint was overall objective response rate by RECIST v1.1, with a null hypothesis of true response rate of 2% versus one‐sided alternative of 15%. Secondary endpoints included 6‐month progression‐free survival (PFS) rate (Fig. 1), median PFS, time to progression (TTP), and overall survival (OS). Safety was evaluated throughout the study. Results: Of 35 patients who enrolled and received treatment, 1 (3%) had a partial response (PR) and 20 (57%) had stable disease (SD). Median TTP, PFS, and OS were 5, 3.9, and 19 months, respectively. The most frequently reported drug‐related serious adverse event was hypertension in three patients. Three deaths were reported on‐study—two due to disease progression and one due to pulmonary embolism not related to ENMD‐2076. Conclusion: The study provided no rationale for further studying ENMD‐2076 as a single agent in FLC.